Pentingnya Statistik Kesehatan dan Sistem Pelaporan di Rumah Sakit - Farhansyah, Fani; Anisa, Desfa; Claudia, Claudia; Mirawati, Dian (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2025)
The hospital reporting system (SPRS) is a system created by the health department that aims to obtain data on all hospital activities throughout Indonesia which is then used as information about the national health situation. The reporting system is crucial, requiring all Indonesian hospitals to submit reports strictly on schedule. One of the reports made by the Hospital is the monthly morbidity report. The monthly morbidity report is a monthly report of disease data containing ICD-10 code data and the distribution of disease cases by age group as well as new or old cases. LB1 data is used by the Health Office to carry out planning, monitoring, and evaluation for follow-up. The data source for 10 outpatient diseases at Awal Bros Hospital comes from daily patient visit reports. The outpatient visit report at Awal Bros Hospital is in the form of electronic data obtained from the outpatient Electronic Medical Record that has been inputted by officers when patients come for treatment or visit on January 1 to 31, 2025. Then the data that has been drawn in the form of Microsoft Excel is filtered and in the pivot table, select the rows diagnosis and value No. Registration then the data is sorted and the data of the Top 10 Most Common Diseases is obtained. At Awal Bros Hospital, back diseases and disc disorders with radiculopathy are the most prevalent, with 2,203 cases. Thus, health workers should prioritize lifestyle counseling to address this significant health issue.